Management of learning activities according to the Philosophy of Sufficiency Economy of Educational Institutions in the Office of Phayao Primary Educational Service Area 1 - Sabphaso, Natthawut (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
The purpose of this research was to study the level and compare the management of learning activities according to the Sufficiency Economy Philosophy of educational institutions in Phayao Elementary Education Service Area Office 1 according to the opinions of administrators and teachers. Classified by education level and school size The sample group was 345 administrators and teachers of schools under Phayao Elementary Education Service Area Office 1, number 345.The research instrument was a 5-level estimation scale questionnaire. The data were analyzed for the mean (Mean), the standard deviation (SD), t-test and F-test Test the pairs using the method of Fisher’sleast significance difference (LSD). The results showed that Management of learning activities according to the philosophy of sufficiency economy Overall, it is at a high level. When considering each aspect, it was found that the aspect with the highest average was the aspect of educational institution management, followed by the student development activities, followed by the curriculum and learning activities, followed by the Educational personnel development and the aspect with the least mean was the outcome/success picture. which all aspects have opinions at a high level. The results of the comparison of the respondents’ opinion levels on the management of learning activities according to the sufficiency economy philosophy of educational institutions in Phayao Elementary Education Service Area Office 1, classified by educational level. Overall, there was no statistically significant difference. when comparing each side It was found that there were no statistically insignificant differences in all 5 aspects, namely, educational institutions management, curriculum and learning activities, learner development activities, educational personnel development, results/success pictures Therefore, the mean pairs were compared using LSD (Least Significant Difference) method. It appeared that there was no difference in pairs which was inconsistent with the hypothesis. and classified according to the size of the school Overall, there was a statistically significant difference at the 0.05 level when comparing each aspect. There were statistically significant differences at the 0.05 level in all 4 aspects, namely, educational institutions management, learner development activities, educational institution personnel development, results/success images. As for the curriculum and learning activities, it was found that there were no statistically significant differences. which is inconsistent with the hypothesis.